2022
DOI: 10.1371/journal.pone.0267752
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis and marker-trait associations in Amaranthus species

Abstract: Amaranth (Amaranthus spp.) is a highly nutritious, underutilized vegetable and pseudo-cereal crop. It possesses diverse abiotic stress tolerance traits, is genetically diverse and highly phenotypically plastic, making it an ideal crop to thrive in a rapidly changing climate. Despite considerable genetic diversity there is a lack of detailed characterization of germplasm or population structures. The present study utilized the DArTSeq platform to determine the genetic relationships and population structure betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Hoshikawa et al [ 48 ] performed genetic diversity analysis among Amaranthus tricolor accessions using genome-wide SNPs and found a set of 5638 SNPs without missing data in 440 accessions. Similarly, Wu and Blair [ 49 ], and Jamalluddin et al [ 50 ] performed genetic diversity analysis and marker-trait associations in amaranths and relative species using Genotyping By Sequencing (GBS) methods. The identification of allelic variations within economically important genes highlights the practical applications of this research in crop improvement programs.…”
Section: Discussionmentioning
confidence: 99%
“…Hoshikawa et al [ 48 ] performed genetic diversity analysis among Amaranthus tricolor accessions using genome-wide SNPs and found a set of 5638 SNPs without missing data in 440 accessions. Similarly, Wu and Blair [ 49 ], and Jamalluddin et al [ 50 ] performed genetic diversity analysis and marker-trait associations in amaranths and relative species using Genotyping By Sequencing (GBS) methods. The identification of allelic variations within economically important genes highlights the practical applications of this research in crop improvement programs.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the development and use of molecular markers such as SSRs ( Suresh S. et al., 2014 ; Delgado and Martín, 2022 ; Vats et al., 2023 ), SNPs ( Jamalluddin et al., 2022 ; Hoshikawa et al., 2023 ); for the diversity analysis but their application in marker-assisted improvement of grain amaranth is very limited. The availability of high-density SNPs information for various amaranth species makes them valuable for genome mapping, analyzing genetic diversity and population structure, constructing ultra-high-density genetic maps, map-based positional cloning, and providing genotypes for genome-wide association analysis ( Xia et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Germplasm from A . hypochondriacus species ( 22 ) and SNP alleles were generated and a genome-wide association study (GWAS) was carried out for the qualitative traits between specific phenotypes and genetic variants within the genome and identified marker-trait associations (MTAs) on 16 amaranthus species. SNP markers were used to produce genetic resources for the phenotyping and development of cultivars.…”
Section: Breeding Behavior and Approachesmentioning
confidence: 99%
“…These crops can be grown in most countries' environmental conditions and are easily available plant sources of micronutrients to alleviate micronutrient malnutrition ( 21 ). There is a need for their genetic improvement and to explore the breeding behavior of these crops, possibilities to create variations in population, and the use of molecular markers to study diversity in amaranth and quinoa ( 22 24 ) ( Table 3 ). We have reviewed genetic mapping studies and DNA barcoding to understand the gene sequence of these crops ( Table 3 ).…”
Section: Introductionmentioning
confidence: 99%